2023
DOI: 10.1002/ldr.4907
|View full text |Cite
|
Sign up to set email alerts
|

A balance among irrigation and fertilization regimes to reduce greenhouse gases emissions from saline and alkaline soils

Sheng Zhang,
Kazem Zamanian,
Sajjad Raza
et al.

Abstract: Agricultural practices of nitrogen and irrigation overuse bring lots of environmental problems, such as greenhouse gases (GHGs) emissions, soil, and water pollution. With the fast expansion of saline and alkaline agricultural soils in the Tarim River Basin, field practice must be very cautious facing water limitations and global warming. The GHGs were measured 1–2 times weekly and water and fertilizer use efficiency were evaluated under five treatments: (1) fallow (Control); (2) no N (kg N ha−1) and no irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…Lyu et al (2021) found that optimized fertilization reduced 49% N 2 O emissions in maize fields in the Hexi Corridor compared with conventional fertilization for 5 years. We also observed a significant positive correlation between N 2 O emissions and WFPS in the present study, which is in agreement with findings from previous studies (Kamran et al, 2023;Li, Ma, et al, 2021;Zhang et al, 2023). Plants also have an important impact on the production and emission of soil N 2 O, which can be mainly divided into two ways: the first way is that plant growth affects the physical and chemical properties, water content and aeration of the soil, thus affecting the diffusion of microbial activity, gas and nutrients in the soil; the second influence pathway is that plants transfer the N 2 O produced in soil through their own aerenchyma, or absorb the watersoluble N 2 O in soil into plants, and then exhaust the gas from plants into the atmosphere through transpiration (Hu et al, 2021).…”
Section: Driver Of Ghg Fluxes Under Different Fertilization Levelssupporting
confidence: 94%
See 4 more Smart Citations
“…Lyu et al (2021) found that optimized fertilization reduced 49% N 2 O emissions in maize fields in the Hexi Corridor compared with conventional fertilization for 5 years. We also observed a significant positive correlation between N 2 O emissions and WFPS in the present study, which is in agreement with findings from previous studies (Kamran et al, 2023;Li, Ma, et al, 2021;Zhang et al, 2023). Plants also have an important impact on the production and emission of soil N 2 O, which can be mainly divided into two ways: the first way is that plant growth affects the physical and chemical properties, water content and aeration of the soil, thus affecting the diffusion of microbial activity, gas and nutrients in the soil; the second influence pathway is that plants transfer the N 2 O produced in soil through their own aerenchyma, or absorb the watersoluble N 2 O in soil into plants, and then exhaust the gas from plants into the atmosphere through transpiration (Hu et al, 2021).…”
Section: Driver Of Ghg Fluxes Under Different Fertilization Levelssupporting
confidence: 94%
“…Emissions of CO 2 had a significant relationship with the soil properties (soil temperature, WFPS and NH 4 + -N) under different fertilization treatment (CO 2 , y = me nT (a + b WFPS +c WFPS 2 ) + f NH 4 + -N + g, R 2 > 0.52; Figure 7). Soil The N fertilization significantly increased cumulative CO 2 emissions (37-176 kg C ha À1 ; Figure 3a,d), and the results are consistent with the results of cumulative CO 2 emissions from maize fields at seedling growth in the range of 21-196 kg C ha À1 under different fertilization input amounts (0-320 kg N ha À1 ; Zhang et al, 2023). The CO 2 fluxes are positively related to soil moisture (p < 0.05) and temperature (p < 0.05; Figure 7), which is probably due to the activity of heterotrophic microorganisms in the soil (Chu et al, 2023).…”
Section: Driver Of Ghg Fluxes Under Different Fertilization Levelssupporting
confidence: 85%
See 3 more Smart Citations